Penciptaan Karya Tari Birama Morse Tubuh Ku sebagai Pilot Project Mencipta Tari Bersama Anak-Anak Tuna Rungu - Jonet Sri Kuncoro; Supendi, Eko; Wijayanto, R. Danang Cahyo; Suroto, Suroto (Abdi Seni, 2025)
The creation of the Morse Code Body dance, as a pilot project to create dance with deaf children, is a community service activity in partnership with the Karanganyar State Special Needs School (SLB Negeri Karanganyar). This work focuses on children with hearing impairments (deaf) in the form of developing movements and beats of the feet, hands, and body. The movements are elaborated with a Morse Code reading system that uses dots (.) and dashes (-) to send and receive messages. This training system uses a demonstration learning method by providing examples directly in front of children supported by a four-step training system. This form of dance work can inspire SLB teachers to create dances and develop the potential and self-confidence of children with hearing impairments in the principle of equality as learning applied to other "normal" children. This program is expected to provide solutions to problems in Karanganyar State Special Needs School and pragmatically to class teachers and children so that they can experience the process of creating dance works and provide performance experiences outside of school. Keywords: creation, dance, morse, stomp, demonstration, training, experience.